Systematic Literature Review: The Effectiveness of Local Culture-Based E-Comic Media in Improving the Learning Outcomes of Pancasila Education for Elementary School Students - Fitriani Fitriani (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to examine the effectiveness of the use of e-comic learning media in improving the learning outcomes of Pancasila Education in elementary school students. This study uses the Systematic Literature Review (SLR) approach by referring to the PRISMA protocol as a guide for literature selection and analysis. Data was obtained through searching for scientific articles published in the 2021–2025 range through the Scopus and Google Scholar databases. From the results of the identification, screening, and feasibility process, as many as seven scientific articles were obtained that were relevant to the focus of the research. The results of the analysis show that research on the implementation of e-comic media in learning Pancasila Education has been carried out in various regions in Indonesia with diverse designs and contexts. In general, the findings of these studies show a positive impact on the use of e-comic media on improving student learning outcomes, both in cognitive aspects, learning motivation, and active involvement in the learning process. In addition, e-comics that are developed by containing elements of local culture or wisdom are considered more contextual and able to instill Pancasila values in a more meaningful way. This study concludes that local culture-based e-comic media has a significant effect on improving the learning outcomes of Pancasila Education for elementary/MI students.